2016
DOI: 10.3892/ijmm.2016.2669
|View full text |Cite
|
Sign up to set email alerts
|

Picrasma quassiodes (D. Don) Benn. attenuates lipopolysaccharide (LPS)-induced acute lung injury

Abstract: Picrasma quassiodes (D.Don) Benn. (PQ) is a medicinal herb belonging to the family Simaroubaceae and is used as a traditional herbal remedy for various diseases. In this study, we evaluated the effects of PQ on airway inflammation using a mouse model of lipopolysaccharide (LPS)-induced acute lung injury (ALI) and LPS-stimulated raw 264.7 cells. ALI was induced in C57BL/6 mice by the intranasal administration of LPS, and PQ was administered orally 3 days prior to exposure to LPS. Treatment with PQ significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Macrophage activation induced by endotoxin leads to the overproduction of inflammatory cytokines, such as IL‐6 and TNF‐α, which are important factors in the pathogenesis of ALI . Based on the above result, we further elucidated whether PGC1α has an anti‐inflammatory effects in LPS‐stimulated RAW264.7 macrophages.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Macrophage activation induced by endotoxin leads to the overproduction of inflammatory cytokines, such as IL‐6 and TNF‐α, which are important factors in the pathogenesis of ALI . Based on the above result, we further elucidated whether PGC1α has an anti‐inflammatory effects in LPS‐stimulated RAW264.7 macrophages.…”
Section: Resultsmentioning
confidence: 94%
“…Oxidative stress is caused by an imbalance between oxidation and anti‐oxidation systems. When neutrophils are activated, they release oxidants and proteases that damage the lungs . ROS play a major pathogenic role in a many human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 activity restores homeostasis and implements cytoprotective defense functions in many pathologic states by the anti-oxidant activity of biliverdin and its metabolite, bilirubin, as well as the anti-inflammatory effects of carbon monoxide (CO) [25,26]. Accumulated research has demonstrated that HO-1 upregulation protects against endotoxin shock and allograft rejection, and attenuates hyperoxia and post-liver transplantation ALI [24,[26][27][28]. Further, HO-1 deficiency is related to a chronic inflammatory state and increased leukocyte recruitment in HO-1 gene-deficient mice [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Heme oxygenase-1 (HO-1) is an inducible stress protein that responds to multiple stressors, including hypoxia, hyperoxia, acidosis, shear stress, and reactive oxygen species [24]. HO-1 activity restores homeostasis and implements cytoprotective defense functions in many pathologic states by the anti-oxidant activity of biliverdin and its metabolite, bilirubin, as well as the anti-inflammatory effects of carbon monoxide (CO) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of ROS and pro-inflammatory cytokines in the BALF. The intracellular levels of ROS were determined using 2',7'-dichlorofluorescein diacetate (DCF-DA; Sigma-Aldrich, St. Louis, MO, USA) as previously described (21). Briefly, BALF cells were washed with PBS and incubated with 20 µM DCF-DA for 10 min at 37˚C.…”
Section: Collection Of Bronchoalveolar Lavage Fluid (Balf) and Determmentioning
confidence: 99%